(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2019)
Rome has been a nation capital only a bit over 150 years, but the rhythm of its history has been marked by its various projects as a modern capital. From the Piani dei Piemontesi and the Centralità of Via Venti Settembre promoted by Quinto Sella, to Francesco Crispi’s Monumental City and to Giovanni Giolitti’s bourgeois city, from the imperial rhetoric persecuted by Benito Mussolini to the democratic recovery of the post WW II, up to the creation of the regions in the 1970s. And now? It has been over thirty years ago now, more or less, since the crisis of Tangentopoli (political corruption exposed in the 90s), no one even tries. Just as Walter Tocci in his historical reconstructions has precisely recorded, the Paths, in which the prospects of a development worthy of a capital seemed could have evolved, have been interrupted. How to reclaim the lines traced by these potential paths, or rather, how to identify new ones, more relevant to the present needs and difficulties. These are the question to which the speakers have tried to answer. And, though starting from a common initial despair to which, we have said, they have tried to give different indications in reference to their study and individual deep thinking on the matter.